2000
DOI: 10.1289/ehp.00108s2343
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response analyses of the carcinogenic effects of trichloroethylene in experimental animals.

Abstract: In lifetime bioassays, trichloroethylene (TCE, causes liver tumors in mice following gavage, liver and lung tumors in mice following inhalation, and kidney tumors in rats following gavage or inhalation. Recently developed pharmacokinetic models provide estimates of internal, target-organ doses of the TCE metabolites thought responsible for these tumor responses. Dose-response analyses following recently proposed methods for carcinogen risk assessment from the U.S. Environmental Protection Agency (U.S. EPA) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…TCA and DCA were also shown to cause liver tumors in rats and mice through induction of peroxisome proliferation in hepatocytes (Herren-Freund et al, 1987). Spermatoxicity studies in rats showed that DCA causes delayed spermiation and morphological abnormalities in residual bodies and testes (Linder et al, 1997 Metabolism of TCE is influenced by many factors, including gender, tissue, and dose (Lash et al, 2000;Rhomberg, 2000) and is closely related to the expression and distribution of enzymes involved in the oxidation and glutathione conjugation pathways. Therefore, understanding the enzymatic basis of TCE metabolism is critical for scrutinizing the mechanisms of action and the human risks of this chemical.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TCA and DCA were also shown to cause liver tumors in rats and mice through induction of peroxisome proliferation in hepatocytes (Herren-Freund et al, 1987). Spermatoxicity studies in rats showed that DCA causes delayed spermiation and morphological abnormalities in residual bodies and testes (Linder et al, 1997 Metabolism of TCE is influenced by many factors, including gender, tissue, and dose (Lash et al, 2000;Rhomberg, 2000) and is closely related to the expression and distribution of enzymes involved in the oxidation and glutathione conjugation pathways. Therefore, understanding the enzymatic basis of TCE metabolism is critical for scrutinizing the mechanisms of action and the human risks of this chemical.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to TCE causes a variety of tumors depending on species and tissues (Green, 2000;Clewell and Andersen, 2004). In mice, TCE causes lung and liver tumors after inhalation or gavage exposure (Rhomberg, 2000). Furthermore, exposure to TCE induces kidney and lung toxicity, and inhibits male fertility (Green et al, 1997;DuTeaux et al, 2004;Forkert et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The carcinogenicity of TCE based on animal models and epidemiologic studies has been reviewed [1,3,5,8]. Increased risks of liver, lung and kidney tumours have been reported in laboratory mice and rats [7,[9][10][11][12]; however, species disparities in TCE metabolism preclude extrapolation to human carcinogenesis. Furthermore, some studies reported no indication of carcinogenic potential in animals [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Rhomberg (19) presents a comprehensive analysis of the liver, lung, and kidney tumor data and pharmacokinetic model-derived dose metrics using default dose-response approaches. Not only does the analysis provide a choice of dose metrics from the two pharmacokinetic models and their uncertainty analyses, which yields four estimates for a single dose metric, it also examines the influence of several metabolites of the cytochrome P450 and glutathione-S-transferase pathways.…”
Section: Scott and Coglianomentioning
confidence: 99%